2012
DOI: 10.1038/aja.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

A novel equation and nomogram including body weight for estimating prostate volumes in men with biopsy-proven benign prostatic hyperplasia

Abstract: Anthropometric measurements, e.g., body weight (BW), body mass index (BMI), as well as serum prostate-specific antigen (PSA) and percent-free PSA (%fPSA) have been shown to have positive correlations with total prostate volume (TPV). We developed an equation and nomogram for estimating TPV, incorporating these predictors in men with benign prostatic hyperplasia (BPH). A total of 1852 men, including 1113 at Tokyo Medical and Dental University (TMDU) Hospital as a training set and 739 at Cancer Institute Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The most usual cause of an enlarged canine or human prostate is BPH, which is an age-related increase in prostate volume and weight [4,5]. BPH is rare in men <30 years, but is present in approximately 50 % of men age 60 or greater [6].…”
Section: Introductionmentioning
confidence: 99%
“…The most usual cause of an enlarged canine or human prostate is BPH, which is an age-related increase in prostate volume and weight [4,5]. BPH is rare in men <30 years, but is present in approximately 50 % of men age 60 or greater [6].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between age, total PSA level, obesity indices and TRUS-measured PV was reported previously [14,25] . Nevertheless, age and BMI were weakly correlated with RTW in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Even in a large population of patients undergoing screening, PSA levels correlate well with the PV measured by a DRE [12] . In addition, recently the metabolic syndrome and obesity have been shown to influence both PSA levels and PV to a great extent [13–16] . Therefore, it was suggested that for an accurate estimation of PV, PSA measurements and obesity indices should be included [13,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Biological PSA variability is known to be <20–46%, based on an intensive repeated PSA testing study . Previous studies have shown that age and PV correlate with PSA value, but not with PSA variability . In the management of BPH patients with significant PSA variability, it would be helpful to bear in mind that dutasteride reduces PSA values by approximately 50% without having an influence on biological PSA variability itself.…”
mentioning
confidence: 99%